Normative Data for the Psychopathy Checklist–Revised in German-Speaking Countries: A Meta-Analysis. (December 2013) - Mokros, Andreas; Hollerbach, Pia; Vohs, Knut; Nitschke, Joachim; Eher, Reinhard; Habermeyer, Elmar
The Psychopathy Checklist–Revised (PCL-R) is the standard assessment method for psychopathic personality traits of offenders. PCL-R norms for German-speaking countries have not yet been published. This study reviews the extant literature on the PCL-R and its screening version in Austria, Germany, and Switzerland. Based on 25 published empirical studies (total N = 4, 254) overall means and standard deviations were estimated using meta-analytic methods. Assuming normality, estimates of norms (percentiles and T -scores) were derived for male offenders with respect to the standard assessment protocol (PCL-R interview plus file review), purely file-based assessments, and the screening version of the instrument. Compared with the North American normative data, estimated sample means were significantly lower for PCL-R standard assessments and for the screening instrument. The present findings may serve as provisional estimates for gauging the level of psychopathic traits of male offenders in Austria, Germany, and the German-speaking parts of Switzerland.